HIRARC PADA BAGIAN MINI BUS PT MEKAR ARMADA JAYA MAGELANG - Agustina Agustina; Mulyono Mulyono (The Indonesian Journal of Occupational Safety and Health, 2017)
Occupational health and safety is mandatory for every worker. Various tools and advanced technology to simplify and speed up an industrial activity, however these activities also have negative impacts which may cause harm to workers. The purpose of this study was to identify the Hazards, Assessment and Risk Management Section Mini Bus (body) in PT Mekar Armada Jaya Magelang Work Accident Prevention. The study was conducted in PT Mekar Armada Jaya Magelang at Jl Mayjen Bambang Soegeng No. 7, Magelang- Central Java. This research was carried out for 8 weeks starting on August 22, 2016 until October 14, 2016. This type of research is observational with cross sectional study. Primary data obtained by observation. While secondary data obtained from the company. The results of this research are largely derived from the potential danger of equipment and working environment and risks to each post terdentifikasi work almost the same as the activity and the equipment used. The conclusion is that there is a risk of potential hazards in PT Mekar Armada Jaya Magelang. So we recommend a special welding training for the regular welder, periodic health examinations and provide cover protector as well as provide smoking areas ( in units ) that separate from the main work sites. Keywords: hazard identification, risk assessment and control of mini bus